2023
DOI: 10.1002/ajh.26803
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of limited‐stage peripheral T‐Cell lymphoma after CHOP(−like) therapy: A population based study of 239 patients from the Nordic lymphoma epidemiology group

Abstract: Peripheral T-Cell Lymphomas (PTCLs) are rare, aggressive lymphomas with poor outcomes, but limited-stage disease is infrequent and not well-described. This study reports outcomes and prognostic factors in limited-stage nodal PTCLs in a binational population-based setting. Patients were identified from the Danish and Swedish lymphoma registries. Adults diagnosed with limited-stage nodal PTCL (stage I-II) and treated with CHOP(Àlike) therapy ±radiotherapy between 2000 and 2014 were included. Medical records were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“… 3 , 6 , 20 , 21 The incidence of stage I(E) disease is reported to be 9.5-11%. 15 , 22 The incidence of stage I(E) PT-CL in this cohort as compared to advanced-stage disease varies per subtype, i.e., patients with AITL rarely have limited-stage disease, which is in line with previous studies. 23 , 24 There has been a remarkable shift in diagnoses between the two time periods from predominantly PTCL NOS to a more or less equal divide between PTCL NOS and ALCL.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“… 3 , 6 , 20 , 21 The incidence of stage I(E) disease is reported to be 9.5-11%. 15 , 22 The incidence of stage I(E) PT-CL in this cohort as compared to advanced-stage disease varies per subtype, i.e., patients with AITL rarely have limited-stage disease, which is in line with previous studies. 23 , 24 There has been a remarkable shift in diagnoses between the two time periods from predominantly PTCL NOS to a more or less equal divide between PTCL NOS and ALCL.…”
Section: Discussionsupporting
confidence: 89%
“…The favorable 5-year OS of patients with stage I(E) PTCL in the current study, as compared to advanced-stage disease previously reported by our group, confirms the results of the Nordic Lymphoma Epidemiology Group that reported on patients with limited-stage (I-II) AITL, ALCL and PTCL NOS (n=239) and found a similar 5-year OS (58%, including stage II patients) compared to 28% for patients with advanced-stage disease in the same time period. 8 , 15 It is unclear whether there was a difference in outcome between stage I and II patients. One might expect a better outcome in our cohort since it only reports on patients with stage I disease, however the Nordic Lymphoma Epidemiology Group only included patients that were treated with at least one cycle of CHOP-like therapy whereas we included all patients with stage I(E) disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and of these, 16% received HDT-ASCT. Median age was 62 years, 5-year OS was 58%, and PFS was 53% (60). As the life expectancy for lymphomas is high and to varying degrees is near that of the background population, it is imperative to shift the research focus from OS alone to an investigation and understanding of treatmentrelated late toxicities.…”
Section: Treatment-related Toxicitiesmentioning
confidence: 99%